Buckle interaction in textured deep subsea pipelines. (17th August 2016) - Karampour, Hassan; Albermani, Faris
Abstract : The paper presents numerical results of lateral buckling, buckle propagation and buckle interaction in textured subsea pipelines, and compares these results to those in conventional cylindrical pipelines. Transient and steady states are used to investigate the interaction between lateral and propagation buckling, and interaction envelopes are presented for textured and cylindrical pipes. It is shown that the textured pipe offers a superior buckle propagation response that is relatively insensitive to imperfection. The interaction between lateral and propagation buckling in cylindrical and textured pipes makes a substantial reduction in buckle initiation pressure, particularly at lower D / t ratios.